Trade and investment effects of forced labour: An empirical assessment - Matthias Busse; Sebastian Braun (Hamburg Institute of International Economics (HWWA), 2002)
This paper explores the international economic effects of forced labour, namely the linkages of forced labour with comparative advantage (trade) and foreign direct investment flows. It discusses several forms and the prevalence of forced labour and presents the results of empirical tests of those linkages. The results show that forced labour may enhance the endowment of unskilled labour. It can thus be expected to improve comparative advantage in unskilled-labour-intensive goods, that is, commodities where the impact of forced labour is likely to be felt most strongly. In contrast, foreign direct investment is negatively linked with forced labour. This result even holds for relatively poor developing countries. – – In dem vorliegenden Beitrag werden die internationalen ökonomischen Auswirkungen der Zwangsarbeit untersucht, das heißt die Beziehung zwischen Zwangsarbeit sowie ausländischen Direktinvestitionen einerseits und komparativen Handelsvorteilen anderseits. Im Mittelpunkt dabei steht zum einen eine Diskussion verschiedener Formen und der Verbreitung von Zwangsarbeit, zum anderen eine empirische Überprüfung dieser Zusammenhänge. Die Ergebnisse zeigen einen positiven Zusammenhang zwischen Ausmaß von Zwangsarbeit und komparativen Handelsvorteilen bei den arbeitsintensiven Industrieprodukten, die vorwiegend von Zwangsarbeit betroffen sind. Auf der anderen Seite investieren internationale Konzerne überwiegend in Ländern, die unterdurchschnittlich von Zwangsarbeit betroffen sind. Dies gilt auch für relativ arme Entwicklungsländer.
Keywords: O19; F23; F14; 330; Forced Labour; Trade; Foreign Direct Investment; Cross-Country Regression Framework; Zwangsarbeit; Komparativer Kostenvorteil; Arbeitsintensität; Direktinvestition; Schätzung; Welt; Entwicklungsländer